Aerosol characteristics in the UTLS region: A satellite-based study over north India. (January 2016) - Srivastava, A.K.; Misra, A.; Kanawade, Vijay P.; Devara, P.C.S.
Abstract: Vertical profiles of aerosol backscatter coefficient and depolarization ratio, obtained from the Cloud–Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellite, were studied in the upper troposphere and lower stratosphere (UTLS) region over North India (21–30° N and 72–90° E), covering the highly polluted Indo-Gangetic Plain (IGP) for one-year period from December 2011 to November 2012. An enhanced aerosol layer was observed between 15 and 18 km altitude, in the vicinity of tropopause, with a broad layer depth of about 2 km. The aerosol layer showed strong seasonal, monthly as well as day and night time variability, with a peak value of backscatter coefficient during monsoon season (∼5.54 × 10 −3 sr −1 in September). The corresponding depolarization ratio indicates anisotropic (non-spherical) nature of particles. The aerosol layer was found to be highly linked with the variability in tropopause height, showing a positive correlation between tropopause height and the height of maximum backscatter coefficient (correlation coefficient of 0.8). However, it was found to be negatively correlated with the integrated backscatter coefficient (IBC), with a correlation coefficient of 0.3. We further analyzed outgoing long-wave radiation (OLR) data during the study period to investigate the link between the observed enhanced aerosol layer in the UTLS region and prevailing deep convective activities over the study region. Low values of OLR during monsoon (about 214 W m −2 ) indicate the occurrence of deep convection over this region, which may cause a large-scale circulation-driven vertical transport of boundary-layer pollution into the atmosphere of UTLS region. Results may have potential implications for better understanding and assessing the chemical and radiative impacts of these aerosols in the tropical UTLS region. Highlights: CALIPSO-derived aerosol profiles are analyzed in the UTLS region over north India. An aerosol layer of about 2 km depth is identified in the vicinity of tropopause. Aerosols in UTLS region are anisotropic (non-spherical) in nature. Enhanced aerosol layer is associated with tropospheric convection through modulation of tropopause.